The Study of Factors Influencing Education Loan Granting and Repayment at Rajabhat Universities in Northern Thailand - Boonchai , Thanat (Community and Social Development Journal, 2022)
The purposes of this research (1) study of factors affecting student loan borrowing at Rajabhat University in the northern region of Thailand. (2) study the factors affecting student loan repayment of Rajabhat University students in the northern region of Thailand. (3) To prepare recommendations for the management of the Rajabhat University Education Loan Fund in the northern region of Thailand. In the study of factors affecting student borrowing, the variables used in the study consisted of Number of Students Borrowing for Education (QLOAN) GPA of Students Before Education Loan (GAP) Domicile of Students (DOMI) Number of Siblings Attended School (NUMSC) Subjects Studied (CURR) Father's Occupation ( F.OCC), maternal occupation (M.OCC), family income (EARN) and father and mother's marital status (MARRY). In the study of factors affecting student loan repayment variables used in The study consisted of Loan Payments (REPAY), Perceived Loan Payments (AWA), and Student Monthly Income (INC) Information on Loan Payments (INFOR), Understanding Borrowing and Repayment Criteria (UND) Gender (SEX) and marital status (STA). From the results of the study, it was found that the grade point average before applying for the loan (GPA) and domicile (DOMI) variables were statistically related same direction to affecting student loan borrowing. In addition DOMI, CURR, NUMSC and GAP had a statistically significant direct relationship to QLOAN. Similarly, the occupation of fathers (F.OCC) and mothers (M.OCC) had a statistically significant correlation with the student's domicile (DOMI). It also found that family income (EARN) had a significant direct effect on the number of siblings attending school (NUMSC). the analysis of factors affecting student loan repayment. results showed that both the INC and AWA variables were statistically related to REPAY. In addition Factors affecting loan repayment (REPAY) are Awareness of Loan Repayment (AWA), with a direct effect on loan repayment (REPAY). Among the factors indirectly affecting loan repayment (REPAY) include information about loan repayment (INFOR) and understanding of borrowing and repayment criteria (UND). Furthermore, the study found that gender (SEX) and marital status (STA) directly affect student monthly income (INC), while student monthly income (INC) does not affect loan payments (REPAY).